Linguistic pathways to the study of literature in the Malaysian ESL Context - Ganakumaran Subramaniam (Penerbit UKM, 2003)
The teaching and learning of literature in English in the Malaysian English as a Second Language (ESL) context has evolved from being a core part of the English language curriculum to a point of near extinction only to re-emerge in the 21 st century in a far stronger form. Given the changed scenario of the teaching and learning of literature in Malaysia since the incorporation of literature as a compulsory and formally tested component of the Malaysian ESL syllabus for secondary schools, it is crucial that consideration be given to teaching and learning approaches. This paper proposes a pedagogical approach via language/linguistic pathways to the teaching and learning of the literature component in the ESL syllabus. The approach propagates that teaching of literature to Malaysian students begins with an introduction to and the awareness of forms and functions of the language in the literary texts. This helps create clear pathways to introduce to learners basic stylistic features in the texts and to consider their roles. Finally the linguistic pathways established through language-based and stylistic approaches may be used to develop specialised reading and interpretative techniques from personal, gender-based, cultural, national and postcolonial positions.